2016
DOI: 10.3354/ab00658
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the seasonal dynamics within the benthic foraminiferal biocoenosis in a tropical monsoon-influenced coastal lagoon

Abstract: Benthic foraminiferal assemblages are widely used as bioproxies for coastal environment monitoring. The present study investigated seasonal variations in live benthic foraminiferal assemblages over a period of 12 mo from the largest coastal lagoon in Asia, which is strongly influenced by tropical monsoons. The investigation revealed an extremely low diversity of benthic foraminiferal assemblages, comprising 12 species, of which 8 were agglutinated. The most dominant taxa throughout the study period belonged to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…populations are generally very abundant throughout the lagoon (Sen and Bhadury, 2016). Besides Ammonia populations, benthic foraminifera species diversity is low in this lagoon (in total 12 species) (Sen and Bhadury, 2016).…”
Section: Study Areamentioning
confidence: 97%
See 4 more Smart Citations
“…populations are generally very abundant throughout the lagoon (Sen and Bhadury, 2016). Besides Ammonia populations, benthic foraminifera species diversity is low in this lagoon (in total 12 species) (Sen and Bhadury, 2016).…”
Section: Study Areamentioning
confidence: 97%
“…Previous reports have documented the presence of six different species of Ammonia (Rao et al, 2000) from the lagoon. However, based on more recent estimates and by incorporating taxonomic revisions Sen and Bhadury (2016) have only identified the presence of three species of Ammonia within the lagoon and their abundance is overwhelming but mostly restricted within the top 2 cm of benthic layer. It has been shown that there are three distinct morphotypes classified as Ammonia T2, T10 and T6 in Chilika lagoon (Sen and Bhadury, 2016).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations